Selective Adaptation Under Globalization: Cultural Resistance and the Maintenance of Pasang Ri Kajang in the Kajang Indigenous Community, South Sulawesi - Sulvahrul Amin; St. Haniah; Tarman Tarman; Lola Abdullaeva (Universitas Negeri Semarang, 2026)
Globalization is often described as a homogenizing force, yet indigenous communities actively interpret and regulate external influences through their own cultural logics. This article examines how the Ammatoa Kajang community of South Sulawesi maintains Pasang Ri Kajang while negotiating pressures from schooling, markets, religion, tourism, and communication technologies. Drawing on anthropological theories of globalization, adaptation, and cultural resistance—particularly Appadurai’s cultural flows, Sahlins’ indigenization of modernity, Steward’s cultural ecology, Scott’s everyday resistance, Barth’s ethnic boundaries, and Lamont and Molnár’s social boundary framework—this study conceptualizes Kajang resilience through two mechanisms: boundary work and Pasang-based moral filtering. Based on qualitative fieldwork in Tana Toa Village, including non-participant observation, unstructured interviews, and documentation, the article shows that the inner–outer spatial division functions as a moral and institutional infrastructure. External elements are not simply accepted or rejected; they are evaluated according to kamase-masea, ecological restraint, honesty, humility, and communal solidarity. Practices considered useful but morally risky are relocated to the outer domain, while the inner customary domain remains protected as a low-tech, ethically regulated space. The study contributes to sociological and anthropological debates on globalization and indigenous resilience by demonstrating that cultural resistance is not isolation from change, but an organized process of selective adaptation rooted in Pasang Ri Kajang.